ANN Based Detection and Location of Severe Three Phase Trip on the Transmission Lines of an Uncontrolled Power System - Muhammad Ali, Suhail; Abdulwahid Salman, Muntaser (Anbar Journal of Engineering Sciences, 2009)
Severe three phase trips are simulated on four arbitrary locations of an uncontrolled power system transmission lines. The responses of three measurable state variables of the system (rotor speed, stator direct axis current, and stator quadrature - axis current) are recorded, and suitable ANNs are trained to detect and locate the positions of the corresponding trips. The paper proves that this method is quick, active and accurate to diagnose and find the locations of that kind of trips.